Misunderstanding Provocation - Pillsbury, Samuel H. (2009)
Provocation is and always has been a compromise rule whose success depends on its ability to appeal to all ideological constituencies, and therefore will always-as long as it lasts-resist the final categorization that this question seeks. As long as provocation involves an inquiry into reasonableness, it will include considerations of justification. As long as it provides for mitigation of punishment based on the difficulty of resisting temptations to violence inspired by strong emotion, it will speak to considerations of excuse